2020
DOI: 10.1128/msphere.00731-20
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and the Gut Microbiota in 10- to 18-Month-Old Children Living in Urban Slums of Mumbai, India

Abstract: In this cross-sectional study, we describe the composition and diversity of the gut microbiota among undernourished children living in urban slums of Mumbai, India, and determine how nutritional status, including anthropometric measurements, dietary intakes from complementary foods, feeding practices, and micronutrient concentrations, is associated with their gut microbiota. We collected rectal swabs from children aged 10 to 18 months living in urban slums of Mumbai participating in a randomized controlled fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 116 publications
1
17
0
5
Order By: Relevance
“…There is a high abundance of Proteobacteria in the feces of obese children, and these bacteria have a significant positive correlation with BMI levels ( 41 , 42 ). Proteobacteria are also relatively abundant among malnourished children and contain many potentially pathogenic species that induce immature intestines or potentially high inflammatory burdens ( 66 ). Of note, physical exercise significantly reduces the abundance of Proteobacteria in obese children ( 67 ).…”
Section: The Relationship Between Pediatric Overweight/obesity and Gu...mentioning
confidence: 99%
“…There is a high abundance of Proteobacteria in the feces of obese children, and these bacteria have a significant positive correlation with BMI levels ( 41 , 42 ). Proteobacteria are also relatively abundant among malnourished children and contain many potentially pathogenic species that induce immature intestines or potentially high inflammatory burdens ( 66 ). Of note, physical exercise significantly reduces the abundance of Proteobacteria in obese children ( 67 ).…”
Section: The Relationship Between Pediatric Overweight/obesity and Gu...mentioning
confidence: 99%
“…In Australian infants aged 6-24 months, dairy intake was positively associated with the Firmicutes to Bacteroidetes ratio but was inversely associated with microbial species richness and diversity [143]. In a recent study of Indian slum-dwelling infants aged between 10 and 18 months, a positive association of fat and iron intake on alpha diversity was observed [144]. In addition, a log ratio of Lactococcus to Anaerococcus was significantly higher in the group who reported consuming oils and fats.…”
Section: From Introduction Of Complementary Foods To Consumption Of Family Foodsmentioning
confidence: 94%
“…Additionally, a factor that may be impacting our results is the baseline gut microbiome in this population, which has been shown to influence response, for example the postprandial glucose response, to dietary interventions in adults [58]. From a preliminary analysis in a subset of children in this cohort, the gut microbiome varied in composition and diversity depending on nutritional status, prior to intervention [59]. There is limited literature on the effect of biofortified crops on the gut microbiome in humans; however, early research in animals such as Gallus gallus have shown positive effects, such as increases in short-chain fatty acids, by consuming iron-and zincbiofortified crops such as common beans [60].…”
Section: Presence Of Unmeasured Factorsmentioning
confidence: 99%